Adsorption of Direct Yellow 9 and Acid Orange 7 from Aqueous Solutions by Modified Pumice - Ahmadian, M.; Yosefi, N.; Toolabi, A.; Khanjani, N.; Rahimi, S.; Fatehizadeh, A. (Asian Journal of Chemistry, 2012)
Adsorption is widely used for removal of different pollutants from wastewater. In this study, modification of pumice adsorbent by detergents and use of modified pumice for eliminating the direct yellow 9 and acid orange 7, from aqueous solutions was investigated. In this study, cetrimide-C, sodium dodecyl sulfate, cetylpyridinium chloride and hexadecyl trimethyl ammonium bromide detergents were used for modification of pumice. All experiments were performed at batch system. The effect of important parameters on adsorption including adsorbent dosage, dye initial concentration, pH solution and contact time were investigated. The experimental data were compared with the Freundlich, Temkin and Langmuir isotherm models and pseudo first order, pseudo second order and Elovich kinetic models. The results showed that with increasing contact time and adsorbent dosage and decreasing dye initial concentration, dye removal efficiency increased. Also by increasing pH from 1 to 7, dye removal efficiency increased. The maximum direct yellow 9 and acid orange 7 adsorption was obtained at pH 6 and 7, respectively. The maximum adsorption capacity of direct yellow 9 and acid orange 7 was 1.22 and 1.08 mg/g, respectively. The rate constant of direct yellow 9 and acid orange 7 adsorption by modified pumice was 0.014 and 0.007 mg/g min, respectively. The results of this study revealed that modified pumice adsorbent can be used as a suitable and effective adsorbent for removal of some dyes from coloured wastewater.